China's transportation sector carbon dioxide emissions efficiency and its influencing factors based on the EBM DEA model with undesirable outputs and spatial Durbin model. (1st January 2022) - Zhao, Pengjun; Zeng, Liangen; Li, Peilin; Lu, Haiyan; Hu, Haoyu; Li, Chengming; Zheng, Mengyuan; Li, Haitao; Yu, Zhao; Yuan, Dandan; Xie, Jinxin; Huang, Qi; et al.
Abstract: The threat of global climate change has caused the international community to pay close attention to atmospheric levels of greenhouse gases such as carbon dioxide. Transportation sector carbon dioxide emissions efficiency (TSCDEE) is a key indicator used to prioritize sustainable development in the transportation sector. In this paper, the epsilon-based measure data envelopment analysis model with undesirable outputs is applied to estimate TSCDEE for 30 provinces in China from 2010 to 2016. We also analyze influencing factors using the spatial Durbin model. Research shows that the overall TSCDEE of the Chinese provinces studied was 0.618, indicating that most regions are still in need of improvements. The provinces with the highest TSCDEE are located in developed coastal regions of China. This study shows that factors such as transportation structure, traffic infrastructure level, and technological progress have prominent positive effects on TSCDEE, while both urbanization level and urban population density exert significantly negative effects on TSCDEE. The findings should have a far-reaching impact on the sustainable development of global transportation. Graphical abstract: Image 1 Highlights: Providing more accurate method in estimating CO2 emissions of the transport sector. Focusing on the transportation sector carbon dioxide emissions efficiency (TSCDEE). Technological progress is the key to improve TSCDEE among different factors in China. Higher mode share of water and rail transport contributes to higher TSCDEE in China. Urbanization presents significantly negative effect on TSCDEE in China.